Peptides from Galleria mellonella against Cryptococcus spp: toxicity in three-dimensional cell cultures and G. mellonella - De Lima Gualque, Marcos William [UNESP]; Vaso, Carolina Orlando [UNESP]; dos Santos, Kelvin Sousa [UNESP]; Galeane, Mariana Cristina [UNESP]; Gomes, Paulo César [UNESP]; Palma, Mario Sérgio [UNESP]; Soares Mendes Giannini, Maria José [UNESP]; Moroz, Andrei [UNESP]; Fusco Almeida, Ana Marisa [UNESP] (Taylor & Francis, 2025)
Aim: This work aimed to test peptides against the planktonic and biofilm form of Cryptococcus spp. and in vitro toxicity using three-dimensional (3D) cells characterized and evaluate in vivo toxicity in Galleria mellonella. Materials & methods: Susceptibility tests were conducted on the planktonic form and biofilm formation. The toxicity of the peptides was evaluated in lung and brain cells in monolayer (2D) and 3D mono- and co-culture, in addition to in vivo analysis with G. mellonella. Results: Susceptibility values ranged from 31.25 to over 250 µg/ml with a fungicidal profile. Regarding toxicity, the PepM2 peptide was not toxic in 3D culture (500 µg/ml). G. mellonella, showed a survival rate of more than 85% In assays with brain and lung cell lines, concentrations ranged from 4 × 104 to 4 × 103 cells/well for brain cells and 1 × 103 cells/well for lung cells. Cocultures used 1 × 105 brain and 1 × 103 lung cells. Conclusion: This study shows that the peptides have great potential against cryptococcosis, and all spheroids were characterized as having a spheroidal and compact structure.
Keywords: antifungal; biofilm; cryptococcosis; Galleria mellonella; lung coculture; three-dimensional culture